Gender Inequality and Growth in Europe - Stephan Klasen; Anna Minasyan (Intereconomics, 2017)
In this paper, we will briefly review the existing literature on the growth impacts of gender gaps and assess its relevance for the European situation. We will show that gender gaps in education in Europe are unlikely to play an important role for economic performance, but that gender gaps in employment appear to impose a significant efficiency cost in European countries where the gaps are large.
Keywords: 330